The Influence of Market Orientation and Digital Marketing on the Performance of Micro, Small, and Medium Enterprises through Competitive Advantage - U.K. Purbasari; Abdul Haeba Ramli; Siti Mariam; Anak Agung Ketut Diatmika (International Publisher (YAPENBI), 2025)
This research analyzes the influence of market orientation and digital marketing on the performance of small and medium enterprises (SMEs), considering the role of competitive advantage as a factor that strengthens that relationship. The study was conducted on SMEs located in Tangerang Regency, involving 140 business actors as main respondents. The results indicate that market orientation has a positive impact on competitive advantage, and digital marketing also positively affects competitive advantage. Furthermore, market orientation positively influences the performance of SMEs, while digital marketing has a positive effect on the performance of SMEs. Competitive advantage can mediate the influence of market orientation on the performance of SMEs. Additionally, competitive advantage can mediate the influence of digital marketing on the performance of SMEs. Thus, all relationships studied in this research show results that are consistent with initial assumptions and provide a positive impact.